Perbandingan Penilaian Tingkat Kesehatan Dengan Metode RGEC Di Perbankan Syariah Indonesia - Nawal Ika Susanti; Ani Rokhaniyah (Journal of Islamic Banking, 2022)
This study aims to compare the assessment of the soundness of banks at PT Bank Muamalat Indonesia, PT Bank Panin Dubai Syariah, PT BTPN, and PT MayBank Syariah using the RGEC method. This research uses descriptive quantitative research that leads to a comparative study. The type of sample used in this study is purposive sampling, the type of judgment sampling is selected using certain considerations that are adjusted to the research objectives or problems developed. The results of calculations using the RGEC method show that PT Bank Muamalat Indonesia from 2016 to 2020 fluctuated, from the predicate very healthy to the predicate healthy and back again to the predicate very healthy. At PT Bank Panin Dubai Syariah from 2016 to 2020 fluctuated from predicate healthy to predicate healthy enough and back again to predicate healthy. And at PT Bank BTPN from 2016 to 2020 able to maintain its rating which is very healthy. Whereas at PT MayBank Syariah from 2016 to 2020 fluctuated from very healthy predicate to healthy predicate and back again to the predicate very healthy. Based on the results of the study, it can be said that there is a comparison of the level of health assessment between PT Bank Muamalat Indonesia, PT Bank Panin Dubai Syariah, PT BTPN, and MayBank Syariah with the RGEC method for the 2016-2020 period.